On‐Surface Synthesis of Ethynylene‐Bridged Anthracene Polymers. (12th March 2019) - Sánchez‐Grande, Ana; de la Torre, Bruno; Santos, José; Cirera, Borja; Lauwaet, Koen; Chutora, Taras; Edalatmanesh, Shayan; Mutombo, Pingo; Rosen, Johanna; Zbořil, Radek; Miranda, Rodolfo; Björk, Jonas; et al.
Abstract: Engineering low‐band‐gap π‐conjugated polymers is a growing area in basic and applied research. The main synthetic challenge lies in the solubility of the starting materials, which precludes advancements in the field. Here, we report an on‐surface synthesis protocol to overcome such difficulties and produce poly( p ‐anthracene ethynylene) molecular wires on Au(111). To this aim, a quinoid anthracene precursor with =CBr2 moieties is deposited and annealed to 400 K, resulting in anthracene‐based polymers. High‐resolution nc‐AFM measurements confirm the nature of the ethynylene‐bridge bond between the anthracene moieties. Theoretical simulations illustrate the mechanism of the chemical reaction, highlighting three major steps: dehalogenation, diffusion of surface‐stabilized carbenes, and homocoupling, which enables the formation of an ethynylene bridge. Our results introduce a novel chemical protocol to design π‐conjugated polymers based on oligoacene precursors and pave new avenues for advancing the emerging field of on‐surface synthesis. Abstract : Gerade verkuppelt : Die Synthese ethinylenverbrückter Anthracen‐Polymere auf Au(111) wird beschrieben. In der Reaktion folgt auf die schrittweise Debromierung eine Homokupplung und Aromatisierung der Chinoid‐Präkursoren, welche mit =CBr2 ‐Gruppen ausgestattet sind.